Impact of EU governance reforms and ECB policy reactions on European government bond markets - (:unkn) unknown (International Economic Society, 2016)
This study aims to search for the impact of EU governance reforms and ECB policy reactions on European government bond markets. To analyze the short-run and long run effects of these reforms and policy reactions, dynamic and static panel data analysis are carried respectively both for PIIGS and 12 euro-zone countries for the period of 2007-2014. The main finding of the empirical study is that monetary policy reactions such as LTRO2 and OMT show immediate negative effects on the government bond yields in the dynamic models both in PIIGS and 12-panel cross-sections. Another finding of the study is that two-pack and the Banking Union had a negative impact on government bond interest rates in the static models both for PIIGS and 12 panel cross-sections. Besides, the analysis shows that the coefficients of the statistically significant variables of PIIGS are much higher than the 12-panel cross-sections’ coefficients, which shows how much the crisis affected the PIIGS countries. © International Economic Society.
Keywords: Dynamic panel analysis; ECB policy measures; Economic governance reforms; Government bond yields; Static panel